Analysis of the Criticism and Defense of Feminism in Social Discourse: A Case of Patriarchal Protection in Sports - Carolina Vázquez Rodríguez; Carmen Martínez Martínez; Inés Herás; Maite Martín-Aragón Gelabert; M.ª Carmen Terol Cantero (Feminismo/s)
The social discourse against feminism has become broader and more explicit. This is generating a controversy that is taking shape in various spheres. Our research shows this controversy by analyzing comments made on digital versions of newspapers about a gift awarded to female squash players at a tournament in the north of Spain in 2019, which included a vibrator, an electric foot file, and hair removal wax. From forty headlines in Spanish, Latin-American and British newspapers, the obtained data set were 1,279 comments. Using a thematic analysis, the comments were classified in six subthemes: gender, offense, politics, patriarchal sexuality, context, and sponsor. The subthemes were grouped in three themes: new misogyny, sexist outrage and corporate advocacy. Two conflicting discourses, both based on two opposites men/women, equality/discrimination, show the social and political conflict in Spanish society. However, the sponsoring company is not questioned. Gender appears as a performative act whose reproduction maintains a tense relationship between what is presented as two different images of women: real/normal versus feminist. Results indicate that the comments reflect deep-rooted attitudes about gender and power, using ambivalent sexism and anti-feminist rhetoric to maintain the status quo, and how corporate sponsorship is presented as a justification mechanism. The debate focuses on the social discourse that pits the feminist model against the patriarchal one, understood as an epistemological stance. From the so-called new misogyny, which presents men as discriminated against, a false parallelism is used that misrepresents the concept of equality, accepts a pre-discursive order on women’s sexuality and neoliberalism through the defence of the corporate market.